2001
DOI: 10.1079/pns2001109
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibiotic resistance and options to replace antimicrobials in animal diets

Abstract: , fax +45 89 99 13 78, email KnudErik. BachKnudsen@agrsci.dk As there is a risk of developing antibiotic resistance, a number of commonly-used antimicrobial growth promoters have been banned in the EU member states. This decision has put new emphasis on using the diet to control enteric bacterial infections of pigs. Dietary carbohydrates constitute a major proportion of diets for pigs, and the carbohydrate fraction has a diverse composition, with different properties in the gastrointestinal tract, some of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…All bacteria found in the swine intestinal tract, however, are potentially affected upon consumption of an antimicrobial agent. Antimicrobial growth promoters in particular, tend not to be well absorbed in the gut and can act directly on the microbiota, mainly on Gram-positive bacteria (Erik and Knudsen 2001).…”
Section: R a F Tmentioning
confidence: 99%
“…All bacteria found in the swine intestinal tract, however, are potentially affected upon consumption of an antimicrobial agent. Antimicrobial growth promoters in particular, tend not to be well absorbed in the gut and can act directly on the microbiota, mainly on Gram-positive bacteria (Erik and Knudsen 2001).…”
Section: R a F Tmentioning
confidence: 99%
“…Both practices increase the risk of infections with pathogenic organisms, and thereby the need for antimicrobial strategies, which has included the common use of antibiotics. [2][3][4][5][6][7][8][9][10][11][12] Although antibiotics may kill some pathogens, the surviving bacteria can develop antimicrobial resistance (AMR) against the class of antibiotic used [13][14][15][16][17][18][19][20] , as well as against other antibiotic classes [21][22][23][24][25][26][27][28][29][30][31] . A retrospective U.S. livestock study found evidence of multidrug resistance (resistance to >3 antimicrobial drug classes) in Escherichia coli that increased from 7.2% to 63.6% between the 1950s and the 2000s 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The growth-promoting effect of antibiotics and zinc oxide likely benefits from the improvement of gut functions and the adjustment of gut microbiota (Smith et al 2002;Xu et al 2018). However, the overuse of antibiotics and zinc oxide has caused severe antibiotic resistance problem and environmental contamination (Erik and Knudsen 2001;Vahjen et al 2015). Therefore, consistent efforts have been made to seek natural substituents of antibiotics and zinc oxide to improve the growth performance of weaning piglets.…”
Section: Introductionmentioning
confidence: 99%